Analisis Kinerja Keuangan Pada Industri Pertahanan Setelah Penambahan Penyertaan Modal Negara (PMN) - Purbaningrat, Bagaskara Wahyu; Deksino, George Royke; Sudiarso, Aries (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
Law of the Republic of Indonesia Number 16 of 2012 on Defense Industry, Article 51 paragraphs 1 and 2, states that the government can inject capital as an investment for the development and increase in production capacity of the Defense Industry owned by the state. One of the state-owned Defense Industry entities is PT PINDAD. State Capital Participation (PMN) is a government investment in State-Owned Enterprises (BUMN) or Limited Liability Companies (PT) with the aim of increasing business capacity and capital structure. Although ideally the financial performance of BUMN improves after receiving PMN, in reality, some BUMN still incur losses. This research is conducted to examine the impact of PMN on the Defense Industry, especially PT PINDAD. This quantitative study uses numerical data from 2014-2019 with horizontal analysis to compare the financial ratios of PT PINDAD during that period. The results showed an improvement in the company's financial condition after receiving PMN, this can be seen from the increase in graphs and trends after 2015 and a significant increase in 2017 because in 2017, PT PINDAD received cash in the amount of Rp. 1,009,025,941,823, but in 2015 there was a decrease in several ratios, due to the disbursement of PMN at the end of the year which requires an appropriate allocation policy.